Revisiting Excellent Customer Service and its Implication on Consistent and Satisfactory Service Delivery: Meninjau Kembali Layanan Prima Pelanggan dan Implikasinya pada Penyampaian Layanan yang Konsisten dan Memuaskan - Amos Ojo Adedeji (J-MARK (Jurnal Manajemen Risiko dan Keuangan), 2023)
Customer relation is one of the most important aspect of business as well as most neglected in the past. With the current waves of development and competition across the companies, it has become household discussion and major researched among other aspect of means of business growth. The paper qualitatively examine the excellent customer service and its implication on consistent and satisfactory service delivery. The study found that consistent excellent customer service delivery leads to high level of productivity, improvement in team work, effective communication, and increase customer satisfaction among others. The work also identified lack of commitment and indifference, poor team work, inconvenient access to support and poor salary scale for staff of service provider among others as barriers to an excellent customer service. The paper concluded by recommending amongst availability of dedicated staff to handle customer issue, strong team work, easy access to support and upgrading of staff remuneration for effective and excellent customer service.